The use of oestrogens in obstetrics and gynaecology - MacPherson, A. I. S. (The University of Edinburgh, 1940)
The term oestrogen is applied to substances which are characterised by a capacity to restore oestrus or heat in the castrate female animal.
The use of oestrogens in obstetrics and gynaecology: written for the Gunning Victoria Jubilee Prize in Gynaecology, 1940